Analysis of Road Traffic Accident Insurance Claim Service Quality at PT Jasa Raharja Office in Pematang Siantar City - Ginting, Margono; Karo-karo, Perlaban; Mayanta , Hendri; Butar-Butar, Diana Florenta; Nainggolan, Anju Bherna D. (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
PT. Jasa Raharja is a government agency engaged in public insurance. The duties and responsibilities are to collect funds through mandatory contributions and donations to be channeled back through compensation services raharja to victims or heirs of victims of traffic accidents on the highway. In the implementation of the provision of compensation funds, many people do not know the requirements for claiming compensation funds at PT. Jasa Raharja (Persero). In addition, the provision of compensation for accident victims is still not appropriate, namely irregular services in handling claims. This happened because PT. Jasa Raharja works closely with partners, namely the police and the hospital. Based on these problems, researchers are interested in conducting research on the Quality of Service for Highway Traffic Accident Insurance Claims at the PT. Raharja Services. This research was conducted at the office of PT Jasa Raharja, Pematang Siantar City. The method used in this research is quantitative method, by using a questionnaire as a means of measuring data. The results showed that all data from the answers of all respondents were in the